Investigation of changes in the Frequency Content of the Ultrasonic Pulse Waves Propagating through Stabilized Soils - Bas, Deniz; Yildirim, Eray (Elsevier, 2025)
This study investigated the changes in the frequency content of ultrasonic waves propagating through stabilized soils under different curing conditions and durations. Additionally, the relationship between the observed frequency changes and the results of soil stabilization was explored. S,ile, Ukrainian, and Pazaryeri clays and organic soil were used, with calcium aluminate cement (CAC) used as a binder. Unconfined compressive strength (UCS) and UPV tests were performed on untreated and stabilized soils under immediately, air-cured, and wet-cured conditions. During the UPV tests, numerical data were obtained by recording the measurement waveforms in the time domain using an oscilloscope. The relationships among the UCS, UPV, arrival times, and spectral amplitudes were examined through regression analysis, yielding significantly high coefficients of determination. The amplitude spectra were obtained by performing a Fourier transform of the waveforms. Significant changes were observed in the amplitude spectra of the untreated and stabilized samples. Untreated soils exhibited heightened attenuation at higher frequencies compared with stabilized soils. All samples exhibited distinct amplitude spectra. The samples with higher UCS exhibited higher amplitudes and predominant frequencies. In organic soils with the lowest UCS, higher frequencies were attenuated, and lower frequencies predominated. In addition, the amplitudes decreased in the frequency domain. These findings highlight the effect of soil stabilization and performance on frequency content.
Keywords: Soil stabilization; Frequency content changes; Ultrasonic pulse velocity; Unconfined compressive strength; Predominant frequency; Spectral amplitude decay